The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1080/09541440802685979
|View full text |Cite
|
Sign up to set email alerts
|

Effects of divided attention in the word-fragment completion task with unique and multiple solutions

Abstract: The Identification-Production Hypothesis predicts that the effect of divided attention (DA) at encoding should be larger when priming tasks involve divergent search processes through many different competitors, because they are supposed to place heavier attentional demands on frontal lobe functions (Gabrieli, Vaidya, Stone et al., 1999). This hypothesis was tested in two experiments using the Word Fragment Completion (WFC) task with unique solutions (which relies on convergent lexical search towards single app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 78 publications
2
12
0
1
Order By: Relevance
“…However, besides the perceptual/ conceptual distinction, the aforementioned tasks also differ in the involvement of identification/production processes. Word-fragment completion is primarily based on identification processes because in most studies (including those by Ruiz et al, 2007, andSoler et al, 2007), the to-be-solved fragments have unique solutions, implying small or no competition during the retrieval phase (Spataro et al, 2010). In contrast, the category generation task is heavily based on production processes (Gabrieli et al, 1999;Vaidya et al, 1997) because participants are instructed to produce the first instances that come to mind in response to a category label: in these conditions, the encoded exemplars must be selected among multiple competing responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, besides the perceptual/ conceptual distinction, the aforementioned tasks also differ in the involvement of identification/production processes. Word-fragment completion is primarily based on identification processes because in most studies (including those by Ruiz et al, 2007, andSoler et al, 2007), the to-be-solved fragments have unique solutions, implying small or no competition during the retrieval phase (Spataro et al, 2010). In contrast, the category generation task is heavily based on production processes (Gabrieli et al, 1999;Vaidya et al, 1997) because participants are instructed to produce the first instances that come to mind in response to a category label: in these conditions, the encoded exemplars must be selected among multiple competing responses.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in word-fragment completion, participants are presented with words at encoding (e.g., scissor) and are later asked to complete unique-solution fragments (e.g., s _ _ ss _ r) with the first words that come to mind. Repetition priming is indicated by higher completion rates for fragments corresponding to previously processed (old) words than for fragments corresponding to previously unprocessed (new) words (Spataro, Mulligan, & Rossi-Arnaud, 2010).…”
mentioning
confidence: 99%
“…We believe that our results are more consistent with the identification/production view. There is some evidence that the negative effects of manipulating attention at encoding are most pronounced during production than identification tasks ( Gabrieli et al, 1999 ), although this remains somewhat controversial (e.g., Light et al, 2000 ; Spataro et al, 2010 ; Prull, 2013 ). The general idea is that the test cues in production tasks (e.g., word-stem completion) are more likely to initiate response competition amongst multiple plausible alternatives (e.g., CARROT and CARPET are valid completions for the word stem CAR___).…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation, however, revealed that attentional manipulations had variable effects across different implicit memory tasks, reducing priming on some tasks (e.g., Gabrieli, et al, 1999; Light, Prull, & Kennison, 2000; Mulligan & Hartman, 1996; Rajaram, Srinivas, & Travers, 2001; Schmitter-Edgecombe, 1999), but not on others (e.g., Bentin, Kutas, & Hillyard, 1995; Mulligan & Hartman, 1996; Mulligan & Peterson, 2008; Smith & Oscar-Berman, 1990; Spataro, Mulligan, & Rossi-Arnaud, 2010; Spataro, Mulligan, & Rossi-Arnaud, 2011). These mixed findings gave rise to various theories aiming to delineate the critical features of priming effects that do or do not require attention at encoding (e.g., Gabrieli, et al, 1999; Mulligan, 1998).…”
mentioning
confidence: 95%